PENGARUH LOVE OF MONEY DAN MACHIAVELLIAN TERHADAP PERSEPSI ETIS MAHASISWA AKUNTANSI: (STUDI EMPIRIS PADA MAHASISWA PRODI AKUNTANSI UNIVERSITAS MALIKUSSALEH) - Yusra, Muhammad; Utami, Chairi (Jurnal Akuntansi dan Keuangan, 2018)
This study aims to know the influence of Love Of Money and Machiavellian on the ethical perception of accounting students of Malikussaleh University. The data used is primary data and the sampling method used is Slovin method. The data of this research are obtained by distributing questionnaires to the respondents. The data obtained are then analyzed by using Multiple Linear Regression, Data Quality Test, Classic Assumption Test, Hypothesis Testing, and Coefficient of Determination. The results of this study indicate that simultaneously Machiavellian and Love Of Money have a significant effect on the ethical perception of accounting students of Malikussaleh Universit which is indicated by the f-count value of 12,600. While f-table (df1 = k, df2 = n-k-1, 5%) = 3.11, or in other words f-count> f-table. Partially, Love Of Money has a significant effect on the ethical perception of accounting students of Malikussaleh University in which indicated by t-count of 3.693 and T table (n-2, 5% two-sided test) = 1.990 where t-count>t-table with a significance value of 0.000 or lower than 0.05. and Machiavellian has a significant effect on the ethical perception of accounting students at -Malikussaleh University which is indicated by t-count = 2.583 and t-table (n-2, 5% two-party test) = 1.990 where t-count> t-table with the significance value 0.012 or lower than 0.05.